ANALYSIS OF SELF-CONTROL AS A PREDICTOR OF HEALTHY BEHAVIOR IN ADOLESCENTS - Sandra Adetya; Yomima Viena S (Universitas Labuhanbatu, 2023)
This study aims to understand the factors that influence healthy habits among adolescents and address the prevalence of unhealthy lifestyles. Given that in this new normal era, health is a major aspect for the world community, especially in Indonesia after the Covid-19 Pandemic. The study adopted a quantitative approach and carried out influence tests to analyze the correlation of self-control and healthy behavior. The research sample was 500 participants with criteria aged between 15-18 years. Samples were taken randomly from several schools in the Jakarta area. Data collection was carried out by distributing questionnaires to determine the level of self-control and healthy patterns of adolescents. This study reveals that adolescents who have good self-control abilities have effective abilities in controlling their emotions. In addition, self-control also acts as an effective tool in triggering and maintaining healthy behavior. In this context, the results of this study have significant scientific impact because they provide strong evidence of the importance of self-regulation in promoting healthy habits in adolescents. The implication is that involving the development of self-control skills in educational programs and adolescent health interventions can be an effective strategy in promoting healthy habits. By taking this self-control factor into account, these programs have the potential to have a significant impact on improving the overall well-being and quality of life of adolescents. Keywords: self control; healthy behavior; teenager.Abstrak Penelitian ini bertujuan untuk memahami faktor-faktor yang mempengaruhi kebiasaan sehat di kalangan remaja serta mengatasi prevalensi gaya hidup yang kurang sehatnya. Mengingat pada era new normal ini, kesehatan menjadi aspek utama bagi masyarakat dunia, khususnya di Indonesia setelah adanya Pandemi Covid-19. Penelitian menjalankan pendekatan kuantitatif serta melakukan uji pengaruh untuk menganalisis korelasi kontrol diri dan perilaku sehat. Sampel penelitian berjumlah 500 partisipan dengan kriteria berumur antara 15-18 tahun. Sampel diambil acak dari beberapa sekolah di daerah Jakarta. Pengumpulan data dilakukan dengan menyebarkan kuesioner untuk mengetahui tingkat kontrol diri serta pola sehat remaja. Penelitian ini mengungkapkan bahwa remaja yang memiliki kemampuan pengendalian diri yang baik memiliki kemampuan yang efektif dalam mengendalikan emosional mereka. Selain itu, kontrol diri juga berperan sebagai alat yang efektif dalam memicu dan mempertahankan perilaku sehat. Dalam konteks ini, hasil penelitian ini memiliki dampak ilmiah yang signifikan karena memberikan bukti kuat tentang pentingnya pengaturan diri dalam mendorong kebiasaan sehat pada remaja. Implikasinya adalah melibatkan pengembangan keterampilan pengendalian diri dalam program-program pendidikan dan intervensi kesehatan remaja dapat menjadi strategi yang efektif dalam mempromosikan kebiasaan sehat. Dengan memperhatikan faktor kontrol diri ini, program-program ini memiliki potensi untuk menghasilkan dampak yang signifikan dalam meningkatkan kesejahteraan dan kualitas hidup remaja secara keseluruhan.Kata Kunci: kontrol diri; perilaku sehat; remaja.